Age-based policy for blood transshipment during blood shortage. (August 2015) - Wang, Ke-Ming; Ma, Zu-Jun
Highlights: We explored the quantitative formulations for properties of inventory structure considering the ages of blood. We proposed an age-based model with two product selection methods for blood transshipment decision-making. The quantity-based policy and the aged-based policy under two product selection methods were compared. Sensitivity of the parameters was observed for operating scenarios with time-varying demand and supply. We revealed the impact of the transshipment decision on inventory management during blood shortage. Abstract: This paper introduces the properties of inventory structure for both rescue and affected banks during blood shortage. An age-based transshipment model is developed, with two preference selection methods for transshipping blood units being presented. Compared to quantity-based policy, the age-based policy under first-in-first-transship is recommended as it can reduce the expired rate more efficiently. Under simulation operating scenarios with time-varying demand and supply, we analyzed the sensitivity of parameters, which include expected supply period, shelf life and blood shortage period. Additionally, this study reveals that the transshipment decision will increase the expired ratio and the overstock ratio after blood shortage.